ENHANCING RISK MITIGATION STRATEGIES IN INNOVATIVE POULTRY SLAUGHTERHOUSES: A HOUSE OF RISK METHOD APPROACH - Widi Astutik; Mujaddid; Januar Kulsaputro; Fole, Asrul; Yanasim, Nurwindy (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The objective of this study is to identify and examine potential risk factors that could disrupt the production process at the Makassar poultry slaughterhouse. In the monthly risk evaluation, RPA currently conducts monthly risk assessments without identifying the root causes of issues. By applying the Current Reality Tree (CRT) and House of Risk (HOR) methods, 28 risk events and 23 risk agents have been successfully identified. After calculations using the HOR model, 12 risk agents were selected, contributing 80% of the total cumulative Aggregate Risk Potential (ARP) as priorities for handling. Thirteen action items have been ranked based on Expected Time to Danger (ETD) using HOR phase 2. As a recommendation, it is advised to implement the findings of this research and focus on departments relevant to the investigated risks. With an innovative and data-driven approach, it is expected that MPS can optimize its operations and enhance business sustainability in facing existing risk challenges.